(untitled) (Proceedings of the International Conference of Geological Engineering Faculty, 2021)
The research area is located in Cigugur, Jadimulya, and Bangunkarya, Pangandaran, West Java. This research is focus on identification and determination the age of calcareous sandstone unit based on foraminifera assemblages. In the research area, the calcareous sandstone unit included in Pamutuan Formation. Based on previous research, regionally the age of Pamutuan Formation is Middle Miocene which deposited with many energy changes and related to the effect of sea level changes. The research method started with literature study followed by field observation by using spotting sampling method, preparation process, and laboratory analysis. Preparation process of foraminifera planktonic performed against six samples of rock by using the method of residues. Samples of foraminifera planktonic are analyzed using binocular microscope and determining the age range of the foraminifera planktonic species based on Bolli classification. The calcareous sandstone unit consists of massive sandstones. The foraminifera planktonic such as Globorotalia opima nana, Catappsydrax dissimilis, Globorotalia obesa, Globigerinoides ruber, Globorotalia mayeri, Sphaerodinellopsis disjuncta, Globigerinoides obliquus, and Globorotalia fohsi peripheroronda are identified in samples. Based on the presence of those foraminifera planktonic marker species, conclude that the calcareous sandstone unit in Pamutuan Formation is indicated to be deposited in the relative age range of N6 to N10 or Early Miocene to Middle Miocene.